Diabetes, arthritis, urinary incontinence, poor self‐rated health, higher body mass index and lower handgrip strength are associated with falls among community‐dwelling middle‐aged and older adults: Pooled analyses from two cross‐sectional Malaysian datasets - Singh, Devinder Kaur Ajit; Shahar, Suzana; Vanoh, Divya; Kamaruzzaman, Shahrul Bahyah; Tan, Maw Pin (Wiley, 2019)
Aim: The identification of risk factors associated with comorbidities and physical fitness might provide pathways for planning therapeutic targets for future falls prevention. Results from large datasets that examined falls risk factors in Asia have been limited. The aim of the present study was to identify the risk factors for falls by pooling data consisting of medical history, physical performance and self-rated health from two large Malaysian epidemiological studies. Methods: Matching variables from the Towards Useful Aging and Malaysian Elders Longitudinal Research datasets related to falls, physical performance and determinants of falls were identified and pooled for analysis. The Timed Up and Go test and dominant handgrip strength tests were used as physical performance measures. Falls were self-reported, and functional status was assessed using activities of daily living. Results: Data of 3935 participants, mean age 68.9 ± 6.8 years, 2127 (54.0%) women and 1807 (46.0%) men were extracted for analyses. In an adjusted model, independent risk factors for falls from this cohort studies were diabetes (OR 1.258), arthritis (OR 1.366), urinary incontinence (OR 1.346), poor self-rated health (OR 1.293), higher body mass index (OR 1.029) and lower handgrip strength (OR 1.234). Conclusions: Although the risk factors that emerged from our analyses were similar to available studies among older adults, the Timed Up and Go test did not appear as one of the risk factors in the present study that included middle-aged adults. Our findings will require confirmation in a prospective study. Geriatr Gerontol Int 2019; 19: 798–803. © 2019 Japan Geriatrics Society